Model Pelatihan Kesiapsiagaan dan Tanggap Bencana Gempa Bumi Berbasis Komunitas: Kajian Komparatif untuk Kecamatan Pemenang, Kabupaten Lombok Utara, Nusa Tenggara Barat - Hendra Wahyudi Pratama; Lalu Rio Mahendra; Baiq Nurhayati Zohrah (UNITY: Journal of Community Service, 2026)
Pemenang District, North Lombok Regency, is one of the areas highly vulnerable to earthquakes due to its location within the active tectonic zone associated with the convergence of the Indo-Australian and Eurasian Plates. The 2018 Lombok earthquake demonstrated that community capacity for disaster preparedness requires continuous strengthening through community-based empowerment approaches. This community service program aimed to improve community knowledge, practical skills, and preparedness for earthquake disasters through community-based training. The implementation included needs assessment, education on earthquake risks and mitigation, evacuation simulations, first aid training, establishment of community disaster preparedness groups, and evaluation using pre- and post-training assessments. The program results indicated substantial improvement in participants' understanding of self-protection procedures, evacuation routes, emergency communication, and community roles in disaster management. The training also strengthened coordination among community members in developing community-based emergency response mechanisms, thereby enhancing local capacity to respond effectively to future earthquake events. These findings demonstrate that participatory disaster preparedness training can significantly improve community resilience and contribute to sustainable disaster risk reduction efforts in Pemenang District, North Lombok Regency.